Cystic Artery Hemorrhage after Cholecystostomy Catheter Exchange Treated with Transcatheter Embolization - Sada, David M.; Metwalli, Zeyad A. (Seminars in Interventional Radiology, 2019)
The pathogenesis of formation of cystic artery pseudoaneurysms is not well understood, but is thought to result from erosion of the cystic artery wall from the adjacent inflammatory process associated with acute or chronic cholecystitis. The presented case discusses an incident of hemorrhage from a cystic artery pseudoaneurysm resulting in a large perihepatic hematoma as well as hemobilia, which developed after a routine cholecystostomy catheter exchange. This was treated with transcatheter embolization using ethylene-vinyl alcohol copolymer.
Keywords: hemorrhage; gallbladder; cholecystitis; cholecystostomy; pseudoaneurysm; interventional radiology